Association between psychological depression and physical health in Chinese empty-nesters during the COVID-19 pandemic - Wang, Shiyi; Fan, Xiaojing; Li, Fang; Zhou, Zhongliang (Frontiers in Psychiatry, 2025)
ObjectivesWith the aging of the population becoming increasingly serious, the phenomenon of empty-nesters is also becoming more and more serious. The psychological problems of the empty-nester elderly are becoming more and more prominent, which may affect their physical health. This study aimed to quantify the association between psychological depression and physical health in the background of the COVID-19 pandemic.MethodsA total of 7,835 empty-nesters over 60 years old were selected from the China Health and Retirement Longitudinal Study in 2020. Depressive symptoms were applied to measure psychological health. The outcome variables of physical health were measured by self-rated health (SRH), chronic disease, and limited basic activities of daily living (BADLs). Binary logistic regression models with odds ratios and 95% confidence intervals (CI) were applied to explore the association between psychological and physical health.ResultsEmpty-nesters with depressive symptoms were 72% less likely to rate their health as good than empty-nesters without depressive symptoms (95%CI: 0.242–0.328). The rates of chronic disease for empty-nesters with depressive symptoms were 1.45 (95%CI: 1.300–1.622) times higher than those without depressive symptoms, and those with depressive symptoms were more likely to have limited BADLs than elderly without depressive symptoms (OR = 3.125, 95%CI: 2.757–3.543).ConclusionWe found that among empty-nesters in China, depressive symptoms were negatively associated with good self-rated health and positively associated with chronic diseases and limitations in BADLs.